The contemporary Mongolian cultural landscape: Cultural influences, language skills, and the impact of foreign cultures - Bayarsaikhan, Khaliunaa (Tudásmenedzsment, 2023)
This article examines the contemporary Mongolian cultural landscape and explores the influence of foreign cultures on Mongolian youth. The study investigates the effects of foreign cultural dominance on Mongolian language proficiency, traditional Mongol script skills, and the appreciation of the mother tongue. Additionally, the article delves into the impact of Korean bubble-culture, social media platforms, Hollywood movies, Japanese anime, and capitalist art on Mongolian youth, with a focus on their potential for escapism and desensitization. Furthermore, the article discusses the clash between traditional Mongolian cultural values and those of dominant foreign cultures, and the resultant devaluation of Mongolian cultural heritage. Ultimately, the study aims to shed light on the challenges and potential alienation faced by Mongolia's cultural landscape.